Prevalence, incidence and predictors of anal high-risk HPV infections and cytological abnormalities in HIV-infected individuals. Issue 1 (January 2015) - Borghetti, Alberto; Cattani, Paola; Maria, Giorgio; D'Onghia, Sara; Santangelo, Rosaria; Marchetti, Simona; Farina, Salvatore; Cauda, Roberto; De Luca, Andrea; Di Giambenedetto, Simona
Summary Objectives Our purpose was to investigate prevalence, incidence and risk factors of anal high risk-HPV infections and cytological abnormalities in HIV-positive individuals. Methods A cohort of consecutively enrolled HIV-positive patients underwent, at baseline visit, a sexual behaviors questionnaire, anoscopy, HPV testing and cytological examination. Hybridization and multiplex-PCR were used for DNA detection and typing; HPV E6-E7 mRNA expression was analyzed in HR-HPV+ patients. Logistic regression was used to assess predictors of HR-HPV infection and anal dysplasia. Results 233 HIV-infected patients were enrolled (81% males, median age 44 years). HR-HPV was detected in 144 anal swabs and showed a positive association with CDC stage C and a negative association with a higher CD4 count and the use of a NNRTI-based antiretroviral regimen. HR-HPV DNA detection and anal warts at baseline were associated to cytological abnormalities; a detectable HIV-RNA independently predicted new onset anal dysplasia at follow-up (incidence 15.4 per 100 patients-year). Incidence of new HR-HPV infection was 44.2 per 100 patients-year. Conclusions The relevance of screening for anal dysplasia in HIV+ patients is emphasized, especially in those with detectable plasma HIV-RNA, anal HR-HPV infection or compromised immunological status.